Diametrically Regular Mappings and Browder's Theorem Without the Endpoint Condition. (11th March 2020) - Panyanak, B.; Suantai, S.
Abstract: In this paper, we introduce the class of diametrically regular mappings and prove that it includes the class of multi-valued mappings having endpoints. We also prove the existence of endpoints and the convergence of an iterative process for mappings of this class. Our approach provides a new idea of proving Browder's theorem without the endpoint condition.